Implementation of the Seguro Popular Program in the "Gonzalo Rio Arronte Medical Complex" in the municipality of Atlixco, Puebla. México (GEON Journal (Management, Organizations and Business), 2017)
Public policies have their fundamental origin in the social right, arise to respond to the conflicts of society. In the case of health problems influenced by the growth of the population, the development of new diseases and epidemics require governments to implement new benefits and treatments, a situation that increases costs and expenses in these services and consequently would limit effective coverage and use of adequate health services. Health policies protect public health; they have as objective to assure the physical and psychic integrity of the individual, and they are specified in a series of services of primary attention, hospitable and of benefits of pharmaceutical type. In México, up to 2003 half of the population enjoyed social security for reasons of their employment status, and, therefore, of legislated health rights. The other half had been marginalized from all types of social protection in health and received services under a strictly assistance scheme. The most important initiative of the alternation governments in regard to the health sector in México is the creation of the Social Health Protection System, which has been called Popular Health Insurance (SPS) aimed at providing economic protection to the population Non-beneficiary, through health insurance, public and voluntary, aimed at reducing out-of-pocket expenses and promoting timely care for health.
Keywords: Public Administration; Municipality; Public Policies; Social Security; Social Assistance; Popular Insurance